INVENTORY OF Musa paradisiaca L. (BANANA) KEPOK IN LUMAJANG REGENCY, MALANG REGENCY AND MAGELANG REGENCY - Suhadi (The East Java Biological Society, 2010)
Banana is fruit containing fairly high nutrition and provides quick reserve energy. The crop grows in tropical area with average rainfall all the year and banana produces at any season. One of the bananas which has high value sale and high competable potency is subvariety of kepok banana. Kepok banana has various subvarieties, these subvarieties have the same morphologies but have different texture appearances thus uneasy to differenciate among them. The texture appearance determines the quality and price of the banana. Often the buyer makes a mistake in choosing subvariety of kepok he wants to, whereas the seller gives him the cheapest subvariety of kepok. Methods we used was method of exploration using free exploration technique step by step without any certain path. There were two phases in the research namely the first phase was carried out in field and the second phase was done in the laboratory. Subvarieties of kepok found in Lumajang Regency are 4 subcultivars, Malang Regency there are 3 and Magelang Regency are subcultivars subcultivars, The sequence of the quality of kapok subcultivars are as follows, red kepok, yellow kepok, big (gede, gilo, gembrot) kepok, and white kepok. Sugestion, organic ferlitilizer should be used in the fertilization of banana cultivation, and conservation of red kepok is highly required.